Long-term boron-deficiency-responsive genes revealed by cDNA-AFLP differ between Citrus sinensis roots and leaves - Lu, Yi-Bin; Qi, Yi-Ping; Lee, Jinwook; Guo, Peng; Ye, Xin; Jia, Meng-Yang; Li, Mei-Li; Chen, Li-Song (Frontiers in Plant Science, 2015)
Seedlings of Citrus sinensis (L.) Osbeck were supplied with boron (B)-deficient (without H3BO3) or -sufficient (10 µM H3BO3) nutrient solution for 15 weeks. We identified 54 (38) and 38 (45) up (down)-regulated cDNA-AFLP bands (transcript-derived fragments, TDFs) from B-deficient leaves and roots, respectively. These TDFs were mainly involved in protein and amino acid metabolism, carbohydrate and energy metabolism, nucleic acid metabolism, cell transport, signal transduction, and stress response and defense. The majority of the differentially expressed TDFs were isolated only from B-deficient roots or leaves, only seven TDFs with the same GenBank ID were isolated from the both. In addition, ATP biosynthesis-related TDFs were induced in B-deficient roots, but unaffected in B-deficient leaves. Most of the differentially expressed TDFs associated with signal transduction and stress defense were down-regulated in roots, but up-regulated in leaves. TDFs related to protein ubiquitination and proteolysis were induced in B-deficient leaves except for one TDF, while only two down-regulated TDFs associated with ubiquitination were detected in B-deficient roots. Thus, many differences existed in long-term B-deficiency-responsive genes between roots and leaves. In conclusion, our findings provided a global picture of the differential responses occurring in B-deficient roots and leaves and revealed new insight into the different adaptive mechanisms of C. sinensis roots and leaves to B-deficiency at the transcriptional level.